An Enterprise Architecture Plan For The Regional Office Of Kementerian Agama Lampung Province Using Feaf - Sutedi Sutedi; Diba Madya Margerefti (Prosiding International conference on Information Technology and Business (ICITB), 2021)
The Regional Office of Kementerian Agama Lampung Province does not yet have a specific system and has not been integrated between sections or work units. In addition, documents and data in each work unit have so far been stored on personal computers (PCs) used by each staff in each work unit, and not all staff have backed up data periodically to offline media (external hard disk). This is of course a high risk of data damage/loss and allows for irregularities to occur in the services provided. This research aims to design enterprise architecture (EA) using FEAF framework to solve the problem. The process carried out from identification of internal  nd external conditions, identification of current and future business needs, creating and clarifying architectural models based on metrics and identification of business architecture, data or information, applications and technologies from the collected data. The results of this research to designing new models by using FEAF EA.Keywords : FEAF, Enterprise Architecture, Kementerian Agama Lampung Province